Civilizational Fork in our Time and Development Alternatives - Bodrunov, Sergey D. (Economy of Regions, 2025)
The signs of a civilizational crisis are becoming increasingly evident and cannot be ignored. Humanity stands at a critical crossroads: either the crisis deepens, potentially leading to severe consequences and the collapse of civilization, or effective strategies are identified and implemented to transform these challenges into opportunities for progress. This article examines the role of technological progress in both exacerbating the crisis and creating the conditions necessary to overcome it. The modern technological revolution is reshaping knowledge-intensive material production, altering the nature of human activity and needs, and laying the groundwork for a transition to a non-economic mode of production and the fulfilment of human needs—noonomy. However, the neoliberal economic paradigm often conflicts with the socio-economic progress driven by recent technological advancements. Addressing this issue does not require dismantling the existing socio-economic system but rather its gradual and systematic transformation. The shift toward noonomy and noocommunity should be recognized as an objective historical trend, guiding the development of a strategic program. This transition will require the emergence—or nooevolution—of new value orientations, or noovalues, grounded in a noocriterial value framework. This framework, rooted in fundamental humanistic principles, will emphasize the development of individuals as bearers of knowledge and culture.